Low-Cost Production of Ca(OH)2 Nanopowder Utilizing Chicken Eggshell as A Single Source - Maddu, Akhiruddin; Tarigan, Putri Andayati Br; Dahlan, Kiagus (Universitas Muhammadiyah Yogyakarta, 2025)
This article reports utilization of chicken eggshell waste as a single source for producing Ca(OH)2 nanopowder by ultrasonic-assisted precipitation method. The effect of heating treatment on the structure, morphology, and functional groups of Ca(OH)2 was investigated. Chicken eggshell waste was calcined to obtain CaO powder and then converted into CaCl2 by dissolving it in an HCl solution. Synthesis of Ca(OH)2 nanopowder was carried out by gradually dropped the NaOH solution into the CaCl2 solution while being irradiated with an ultrasonic wave. The heating treatment was carried out at 100oC, 200oC, and 400oC, respectively. Ca(OH)2 samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and infrared spectroscopy. X-ray diffraction analysis showed that the Ca(OH)2 samples had a single crystal phase, and the crystal size varied with different heating temperature. Surface morphology showed the fine microstructure of Ca(OH)2 samples, finer as temperature increased. FTIR analysis showed that the functional groups appeared which indicated that the chemical structure of the Ca(OH)2 compound had been formed.